Children and Peace From Research to Action - Balvin, Nikola; Christie, Daniel J. (Peace Psychology Book Series,, 2020)
This open access book brings together discourse on children and peace from the 15th International Symposium on the Contributions of Psychology to Peace, covering issues pertinent to children and peace and approaches to making their world safer, fairer and more sustainable. The book is divided into nine sections that examine traditional themes (social construction and deconstruction of diversity, intergenerational transitions and memories of war, and multiculturalism), as well as contemporary issues such as Europe's "migration crisis", radicalization and violent extremism, and violence in families, schools and communities. Chapters contextualize each issue within specific social ecological frameworks in order to reflect on the multiplicity of influences that affect different outcomes and to discuss how the findings can be applied in different contexts. The volume also provides solutions and hope through its focus on youth empowerment and peacebuilding programs for children and families. This forward-thinking volume offers a multitude of views, approaches, and strategies for research and activism drawn from peace psychology scholars and United Nations researchers and practitioners. This book's multi-layered emphasis on context, structural determinants of peace and conflict, and use of research for action towards social cohesion for children and youth has not been brought together in other peace psychology literature to the same extent. Children and Peace: From Research to Action will be a useful resource for peace psychology academics and students, as well as social and developmental psychology academics and students, peace and development practitioners and activists, policy makers who need to make decisions about the matters covered in the book, child rights advocates and members of multilateral organizations such as the UN.